PRODUCTION OF OXYTETRACYCLINE BY DIFFERENT MUTANTS OF STREPTOMYCES RIMOSUS INDUCED BY PHYSICAL MUTAGENS IN A DATE MEDIUM (Biological Sciences - PJSIR, 2022)
Sixty seven mutants produced by different physical mutagens were surveyed for antibiotic formation. One mutantout of 18 UV -mutants produced higher antibiotic titres than the initial organism, while in case of the 49 x-rays mutants,none of the mutants produced antibiotic yield more than the parent organism. UV irradiation gave the highest totalauxotrophic mutants percentage